VBORNET gap analysis: Mosquito vector distribution models utilised to identify areas of potential species distribution in areas lacking records. - Schaffner, F; Versteirt, V; Van Bortel, W; Zeller, H; Wint, W; Alexander, N (Ubiquity Press, 2016)
This is the second of a number of planned data papers presenting modelled vector distributions produced originally during the ECDC funded VBORNET project. This work continues under the VectorNet project now jointly funded by ECDC and EFSA. Further data papers will be published after sampling seasons when more field data will become available allowing further species to be modelled or validation and updates to existing models. The data package described here includes those mosquito species first modelled in 2013 & 2014 as part of the VBORNET gap analysis work which aimed to identify areas of potential species distribution in areas lacking records. It comprises three species models together with suitability masks based on land class and environmental limits. The species included as part of this phase are the mosquitoes Aedes vexans, Anopheles plumbeus andCulex modestus. The known distributions of these species within the area covered by the project (Europe, the Mediterranean Basin, North Africa, and Eurasia) are currently incomplete to a greater or lesser degree. The models are designed to fill the gaps with predicted distributions, to provide a) assistance in targeting surveys to collect distribution data for those areas with no field validated information, and b) a first indication of the species distributions within the project areas.